2017
DOI: 10.2169/internalmedicine.56.7971
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Morning Glycemic Variability and Patient Characteristics Using Continuous Glucose Monitoring Data in Patients with Type 2 Diabetes

Abstract: Objective To investigate the relationship between patient characteristics and morning glycemic variability. Methods We retrospectively evaluated 106 patients with type 2 diabetes who underwent continuous glucose monitoring during admission. The highest postprandial glucose level (within 3 hours after breakfast; ‘highest level’), the time from the start of breakfast to the highest postprandial glucose level (‘highest time’), the difference between the pre-breakfast and highest postprandial breakfast glucose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Cognitive impairment is also an essential factor in predicting hypoglycemia in elderly inpatients with T2DM, and cognitive impairment increases the risk of hypoglycemia. For older adults with T2DM, cognitive impairment can lead to di culties in controlling blood glucose and identifying and treating hypoglycemia, and frequent hypoglycemia attacks can further exacerbate cognitive decline, forming a vicious cycle [41] . In addition, hypertension is a predictor for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is also an essential factor in predicting hypoglycemia in elderly inpatients with T2DM, and cognitive impairment increases the risk of hypoglycemia. For older adults with T2DM, cognitive impairment can lead to di culties in controlling blood glucose and identifying and treating hypoglycemia, and frequent hypoglycemia attacks can further exacerbate cognitive decline, forming a vicious cycle [41] . In addition, hypertension is a predictor for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia among older individuals can lead to falls, bone fractures, depression, arrhythmias and reduced quality of life, with severe hypoglycemia being a risk factor for dementia and cognitive decline . Although only few studies have directly compared the frequency of hypoglycemia between young and old patients with type 2 diabetes, several reports using multivariate analysis have shown that age is not a factor associated with hypoglycemia . However, compared with younger patients with type 2 diabetes, older patients with type 2 diabetes have fewer autonomic and central nervous symptoms at the time of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although only few studies have directly compared the frequency of hypoglycemia between young and old patients with type 2 diabetes, several reports using multivariate analysis have shown that age is not a factor associated with hypoglycemia. 15,16 However, compared with younger patients with type 2 diabetes, older patients with type 2 diabetes have fewer autonomic and central nervous symptoms at the time of hypoglycemia. It is possible that a great deal of undiagnosed hypoglycemia might have appeared.…”
Section: Discussionmentioning
confidence: 99%
“…In any case the following are necessary in order to reduce increases in post‐breakfast glucose levels: (i) adjusting treatment to avoid nocturnal hypoglycemia when nocturnal hypoglycemia causes increased morning glucose levels; and (ii) decreasing post‐breakfast glucose levels directly by adjusting treatment. Regarding (ii), knowledge of a patient's morning glycemic variability status is important for improving increased glycemic variability over 24 h. We focused on using patient characteristics to predict morning glycemic variability, and we have reported the relationship between patient characteristics and morning glycemic variability in a previous study . In that study, higher age and lower body mass index (BMI) were observed to be associated with higher highest increased post‐breakfast glucose levels.…”
Section: Introductionmentioning
confidence: 99%